IVF and ICSI in Male Infertility: Update on Outcomes, Risks, and Costs - Edward Karpman; Daniel H. Williams; Larry I. Lipshultz (The Scientific World Journal)
Assisted reproductive technology with intracytoplasmic sperm injection (ICSI) is becoming an international panacea for couples struggling with infertility. The increasing popularity of these techniques and the data generated has given us a better understanding of the efficacy, consequences and costs of these procedures. There still remain many unanswered questions and controversies surrounding the use of IVF and ICSI. Increased experience, better refinement of these techniques and clearer indications for IVF and ICSI will inevitably minimize the risks associated with this procedure.